On the Significance of Antithrombin-III, α2-Macroglobulin, α2-Antiplasmin, Histidine-Rich Glycoprotein, and Protein C in Patients with Acute Myocardial Infarction and Deep Vein Thrombosis - Gram, Jørgen; Jespersen, Jørgen (Thrombosis and Haemostasis, 1985)
In a longitudinal study the plasma levels of antithrombin-III, α2-macroglobulin, α2-antiplasmin, histidine-rich glycoprotein, and protein C were followed in two groups of patients with acute myocardial infarction (AMI), one with and one without deep vein thrombosis (DVT). None of the sequentially studied periods revealed significant differences between the two groups of patients. However, small but consistently higher levels of histidine-rich glycoprotein in patients with DVT suggested the existence among patients submitted for myocardial infarction of a subgroup with increased thrombophilic potential. It was concluded that the inhibitors studied are of little value as possible indicators of the presence of DVT at early stages of the disease when clinical signs are absent and when antithrombotic prophylaxis should preferably be initiated.
Keywords: Deep vein thrombosis; Antithrombin-III; α2-macroglobulin; α2-antiplasmin; Histidine-rich glycoprotein; Protein C